SOWING DEPTH IN EMERGENCE OF Senna occidentalis SEEDLING - Solano Neto, A.; Yamashita, O. M.; Moro, F. A. C.; Silva, W. M.; Carvalho, M. A. C.; Rocha, A. M. [UNESP]; Oliveira, L. C. A. [UNESP]; Domingues, S. C. O.; Rabelo, H. O. (Centro Federal Educacao Tecnologica Rio Grande Norte, 2021)
Senna occidentalis, popularly known as coffee senna in Brazil and regions of South America, is a very problematic weed species both in pasture areas and in annual and perennial crops. Management strategies for this species range from the use of harrows to the practice of cultural management with straw and the use of herbicides. The knowledge of the capacity of this species to emerge from great depths becomes important for the adoption of preventive management strategies. The research aimed to verify at what depth this species emerges in Amazonian soil. It was found that even at 10.0 cm deep, the seedlings managed to emerge and form with the same height as those kept close to the soil surface. For the species, the best depths were between 2.0 and 6.0 cm, indicating that these conditions favor its development.
Keywords: Weed; Coffee senna; germination